Overexpression of the pathogen-inducible wheat TaWRKY45 gene confers disease resistance to multiple fungi in transgenic wheat plants - Bahrini, Insaf (Breeding science, 2011)
Recently we cloned and characterized the gene for the wheat transcription factor TaWRKY45 and showed that TaWRKY45 was upregulated in response to benzothiadiazole (BTH) and Fusarium head blight (FHB) and that its overexpression conferred enhanced resistance against F. graminearum. To characterize the functional role of TaWRKY45 in the disease resistance of wheat, in the present study we conducted expression analyses of TaWRKY45 with inoculations of powdery mildew and leaf rust and evaluated TaWRKY45-overexpressing wheat plants for resistance to these diseases. TaWRKY45 was upregulated in response to infections with Blumeria graminis, a causal fungus for powdery mildew, and Puccinia triticina, a causal fungus for leaf rust. Constitutive overexpression of the TaWRKY45 transgene conferred enhanced resistance against these two fungi on transgenic wheat plants grown under greenhouse conditions. However, the expression of two resistance-related genes, Pm3 and Lr34, was not induced by the inoculation with powdery mildew in TaWRKY45-overexpressing wheat plants. These results suggest that TaWRKY45 is involved in the defense responses for multiple fungal diseases in wheat but that resistance involving TaWRKY45 differs from at least Pm3 and/or Lr34-related resistance. Our present and previous studies indicate that TaWRKY45 may be potentially utilized to improve a wide range of disease resistance in wheat